A Unique Interaction of IVS-I-1 (G>A) (HBA2: c.95+1G>A) with Hb Adana (HBA2: c.179G>A) Presenting as Transfusion-Dependent ?-Thalassemia - Alauddin H.; Kamarudin K.; Loong T.Y.; Azma R.Z.; Ithnin A.; Jalil N.; Razak N.-F.; Koh-Xuan-Rong D.; Ismail E.; C-Khai L.; Abdul Latiff Z.; Alias H.; et al. (Taylor and Francis Ltd, 2024)
Indexed by WOS/Scopus/ERA